2021
DOI: 10.24853/mmj.2.2.55-61
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Birthing Ball on Duration of the First Stage of Labour in Primigravida at Utama Barokah Clinic, Bandung City in 2021

Abstract: Background: Labour and birth are physiological and normal events. The process is considered to be normal if it takes 37-42 weeks without any complications. Non-pharmacological methods to speed up the progress of labour include birthing ball exercises. The Birthing ball exercise is a technique to help the progress of labour that can be used during the first stage of labour. Until now, birthing balls are not widely known and not common, even though birthing balls are very effective in accelerating the birth proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…Both birth balls utilized in this study were found to affect the pain perception levels, but the spherical birth balls were found to have the highest effect. Several studies that investigated the effect of the use of birth balls on pain have shown that the use of the balls reduced labor pain significantly (7,9,17,30,(32)(33)(34)(35)(36)(37)(38)(39). A randomized study indicating that nonpharmacological methods reduced the severity of labor pain reported that the use of a peanut ball in 4-5 cm cervical dilatation, massage application in 5-6 cm cervical dilatation, and a hot shower after 7 cm cervical dilatation reduced labor pain significantly (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both birth balls utilized in this study were found to affect the pain perception levels, but the spherical birth balls were found to have the highest effect. Several studies that investigated the effect of the use of birth balls on pain have shown that the use of the balls reduced labor pain significantly (7,9,17,30,(32)(33)(34)(35)(36)(37)(38)(39). A randomized study indicating that nonpharmacological methods reduced the severity of labor pain reported that the use of a peanut ball in 4-5 cm cervical dilatation, massage application in 5-6 cm cervical dilatation, and a hot shower after 7 cm cervical dilatation reduced labor pain significantly (40).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study showed that free positioning with birth balls could directly reduce women's labor pain by enlarging the dimensions and mobility of pelvic and fetal positions (38).…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the causes of maternal mortality worldwide. In contrast, mothers die from prolonged labor in Indonesia, where the rate is the highest in ASEAN (359 per 100,000 live births) (Oktafiani, 2021) In 2021, the Katibung Health Center saw an increase in the number of mothers giving birth, with 811 mothers giving birth and 21 mothers giving birth (a rate of 2.6%) experiencing problems. In addition, there were no maternal deaths in Katibung Health Center in either 2020 or 2021.…”
Section: Introductionmentioning
confidence: 99%